PERBANDINGAN KINERJA NPL SERTA FAKTOR-FAKTOR YANG MEMPENGARUHI - Mulia Alim; Hesty Erviani Z (Universitas Muhammadiyah Tangerang, 2017)
Non performing loans are defined as risks associated with the likelihoodof failure of the client to pay its obligations or the risk that the debtorcan not repay the debt. NPLs reflect credit risk, the smaller the NPL theless the credit risk borne by the bank. In order for the bank's value tothis ratio to be good, Bank Indonesia sets the net NPL ratio below 5%.In addition to domestic and foreign economic problems, it turns out thatsome of the financial ratios held by the Bank can give effect to thechange in NPL value at Commercial Banks. This study aims to analyzethe influence of liquidity and solvency ratios (LDR, LAR and DER), theamount of credit, inflation rate and BI Rate to the ratio of nonperformingloans (NPL) to commercial banks and simultaneouslyanalyze the comparison of NPL Performance in state-owned CommercialBanks (BUMN) with Private Banks domestic (BSDN).